Evaluación para la obtención de resina epoxica a partir de aceite de ricino a nivel laboratorio (2016)
The present research had as objective to evaluate the behavior of castor oil as raw material for epoxy resin obtaining. For this was used a transamination process of castor oil throught diethylenetriamine (DETA) and the final product was used as aminic hardener in epoxy resins obtaining. For this was used a 250 ml glass reactor. To this graduate project the procedure was realized at three temperature conditions (65ºC, 75ºC y 85ºC) and three relations of castor oil vs DETA (1:1, 1:2, 1:3). After had obtained the aminic hardener conversion percent was measured according the process used by the company and were used the tests which had a resultant greater than 90% and was made a viscosity characterization.